Quantitative method for determining serum alkaline phosphatase isoenzyme activity II. Development and clinical application of method for measuring four serum alkaline phosphatase isoenzymes. - Shephard, M D (1986)
A method for quantitating the liver, bone, intestinal and placental alkaline phosphatase activity of serum, using an algorithm for converting selective inactivation by guanidine hydrochloride, L-phenylalanine, and heat into equivalent isoenzyme activity is described. The method can individually quantify mixtures of isoenzymes to within a margin of 3%; it has acceptable reproducibility and has been used to develop both age and sex related reference ranges. Analysis time is about 30 minutes. The clinical reliability of this method has been shown in a study of 101 patients, in 79% of whom isoenzyme results were compatible with the final clinical diagnosis; in 10% a clinical diagnosis resulted from isoenzyme analysis, and in a further 11% the source of the increased alkaline phosphatase activity was identified and supported by electrophoresis, with a definite clinical diagnosis yet to be made.